Hubungan Antara Kepatuhan Kontrol dan Minum Obat Pasien Diabates Melitus Tipe II dengan Kejadian Komplikasi di Rumah Sakit Aura Syifa Kediri - Jordanio Viari Palallo; Febtarini Rahmawati; Stephani Linggawan (Pusat riset dan Inovasi Nasional, 2026)
Type 2 diabetes mellitus is a chronic disease characterized by impaired glucose metabolism resulting from insulin resistance or relative insulin deficiency. It is one of the major global health problems and can lead to various serious complications if not managed properly. Complications such as neuropathy, nephropathy, retinopathy, and diabetic ulcers frequently occur as a consequence of inadequate blood glucose control, which is strongly influenced by patients' adherence to medication and routine follow-up visits. This study aimed to determine the relationship between medication adherence, follow-up adherence, and the occurrence of complications among patients with type 2 diabetes mellitus at Aura Syifa Hospital, Kediri. This study employed an analytical observational design with a cross-sectional approach. A total of 35 patients were selected using purposive sampling. Data were collected from medical records and analyzed using Fisher's Exact Test. The results revealed a significant relationship between medication adherence and the occurrence of complications (p < 0.002), as well as between follow-up adherence and complications (p = 0.027). These findings indicate that patients who are non-adherent to medication and routine follow-up are at a higher risk of developing complications. Therefore, strengthening patient education, supervision, and adherence monitoring systems is essential in healthcare services to prevent disease progression and reduce the incidence of complications. This study is expected to serve as a basis for developing educational interventions and primary healthcare policies aimed at improving the management of patients with type 2 diabetes mellitus.